Impact of security breach on the upstream delay performance of next generation gigabit passive optical networks - F. M. Atan; Nadiatulhuda Zulkifli; S. M. Idrus; N. A. Ismail; A. M. Zin (Institute of Advanced Engineering and Science, 2019)
The next generation passive optical networks (NG-GPON) such as long reach GPON is the future-proof solution to answer the continuous demands for access user bandwidth and network expansion. However, security which is yet to be addressed in NG-GPON needs urgent attention as it will become more critical due to much longer distance, denser user population and more network elements. In addition, the longer propagation delay in NG-GPON can also lead to a more complex bandwidth allocation mechanism that is expected to operate in a dynamic manner. Among the highlights of recommendations for future implementation are improvements in the security aspect and the use of dynamic bandwidth allocation (DBA) algorithm that suit the characteristics of long reach GPON. Current PON is exposed to degradation attack, a security breach that can harm how bandwidth fairness mechanism among ONUs work. Thus, this project proposes a secured DBA mechanism for NG-PON that could overcome this particular threat. In specific, a detection phase will be included in the DBA mechanism to sense and subsequently mitigate abnormal behaviours among ONUs that are harmful to the goal of DBA i.e. to ensure QoS among ONUs and traffics. At the same time, careful attention is given on the delay parameter as it is a critical parameter that can affect DBA performance in long reach GPON. In this paper, preliminary analysis is shown that reveal how possibility of threats increase with increasing of distance and network elements.